Dialkyl Sulfobetaine Surfactants Derived from Guerbet Alcohol Polyoxypropylene–Polyoxyethylene Ethers for SP Flooding of High Temperature and High Salinity Reservoirs. Issue 3 (14th February 2021) - Chen, Zhao; Li, Yuanli; Liu, Xiaomin; Cui, Zhenggang
Abstract: Dialkyl hydroxypropyl sulfobetaine (HSB) surfactants, C16 GA‐(PO)5 ‐(EO)3 ‐HSB and C24 GA‐(PO)10 ‐(EO)10 ‐HSB, were synthesized from Guerbet alcohols (GA) polyoxypropylene–polyoxyethylene (PO‐EO) ethers and their behaviors in surfactant‐polymer (SP) flooding of high temperature and high salinity reservoirs were examined and compared with their anionic hydroxypropyl sulfonate (HS) counterparts, C16 GA‐(PO)5 ‐(EO)3 ‐HS and C24 GA‐(PO)10 ‐(EO)10 ‐HS. The PO‐EO chain embedded improves their aqueous solubility, and the sulfobetaines show better salt resistance than sulfonates. For a reservoir condition of total salinity 19, 640 mg L −1 and 60–80°C, C16 GA‐(PO)5 ‐(EO)3 ‐HSB alone can reduce crude oil/connate water interfacial tension (IFT) to ultralow at 0.25–5 mM, which can be further widened to 0.1–5 mM by mixing with dodecylhexyl (C12+6 ) glyceryl ether hydroxypropyl sulfobetaine (C12+6 GE‐HSB), a slightly hydrophobic surfactant. C24 GA‐(PO)10 ‐(EO)10 ‐HSB is more hydrophobic for the specified reservoir condition, however, by mixing with hexadecyl dimethyl hydroxypropyl sulfobetaine (C16 HSB), a hydrophilic surfactant, ultralow IFT can also be achieved at a total concentration of 0.25–5 mM. The anionic counterparts can also reduce IFT to ultralow by mixing with C12+6 GE‐HSB and C16 HSB, respectively. Moreover, the optimum binary mixture, C16 GA‐(PO)5 ‐(EO)3 ‐HSB/C12+6 GE‐HSB at a molar fraction ratio of 0.6/0.4, can keep the negatively charged solid surface water‐wet ( θ w  = 12–23°) in a wide concentration range, and can still achieve ultralow IFT after stored at 90°C for 90 days (initially 5 mM), which overall are favor of improving oil displacement efficiency at high temperature and high salinity reservoir conditions.